2014
DOI: 10.1007/s12671-014-0330-2
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Mindfulness Training for Mental Health Staff: Organizational Context and Stakeholder Perspectives

Abstract: Occupational stress and burnout adversely impacts mental health care staff well-being and patient outcomes. Mindfulness training reduces staff stress and may improve patient care. However, few studies explore mental health setting implementation. This qualitative study used focus groups to evaluate stakeholders’ perceptions of organizational factors affecting implementation of an adapted version of Mindfulness-Based Stress Reduction (MBSR) for staff on adolescent mental health units. Common facilitators includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
62
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(65 citation statements)
references
References 46 publications
2
62
0
1
Order By: Relevance
“…However, Hallman et al ( 2017 ) found that only a few HCPs used the allocated meditation time and Brady et al ( 2012 ) reported a 30% attrition rate due to the varying work schedule demands of the unit. Bryon et al ( 2015 ) identified several barriers to the implementation of mindfulness training for HCPs working within psychiatric inpatient units, which included limited time for staff to attend training sessions, insufficient cover to allow staff to participate in the sessions without using personal time and inadequate preparation for the new initiative on some units. Due to the practical difficulties and time restrictions often faced by HCPs, shorter MBSR programmes incorporated into the regular working schedules of staff have been recommended to reduce attrition rates (Shapiro et al 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, Hallman et al ( 2017 ) found that only a few HCPs used the allocated meditation time and Brady et al ( 2012 ) reported a 30% attrition rate due to the varying work schedule demands of the unit. Bryon et al ( 2015 ) identified several barriers to the implementation of mindfulness training for HCPs working within psychiatric inpatient units, which included limited time for staff to attend training sessions, insufficient cover to allow staff to participate in the sessions without using personal time and inadequate preparation for the new initiative on some units. Due to the practical difficulties and time restrictions often faced by HCPs, shorter MBSR programmes incorporated into the regular working schedules of staff have been recommended to reduce attrition rates (Shapiro et al 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nurses were trained in mindfulness before providing this therapy (Wolf et al, 2016). A previous study conducted by Byron et al (2014) explains that nurses who have been trained could support the faster recovery of patients. Furthermore, in this study psychiatric nurses have been able to emphasize the components of mindfulness therapy, especially the comfort stage and self-health targets.…”
Section: Discussionmentioning
confidence: 99%
“…force. Employee training [4][5][6] refers to the organization of the organization's development goals and the individual development goals of the employees, based on the planned organization of employees to carry out targeted learning and training, so as to improve the staff's knowledge reserves, improve employees The work skills, improve the work attitude of employees, and motivate employees' sense of innovation, so that employees can better be qualified for their work in a form of human resource management. For SMEs, the ability to grasp market opportunities is the determining factor for the development and growth of SMEs.…”
Section: Introductionmentioning
confidence: 99%